(untitled) (Interdisciplinary Studies Journal, 2026)
With the aim of understanding the phenomenon of the judicialization of public health, the quantitative, retrospective, cross-sectional descriptive study analyzed 749 cases from the Childhood and Youth Health 4.0 Center of the Court of Justice of Pernambuco. This Center has jurisdiction over the processing and adjudication of childhood and youth health rights claims against the State of Pernambuco or its constituent municipalities. The study focuses on the causes of action, the relief sought, and the influence exerted by the claimant’s gender. The findings of the research show that 61.9% of the petitioners were male, the prevalent cause of action was related to Autism Spectrum Disorder, with 301 requests; included in the rating “Mental, behavioral or neurodevelopmental disorders” (40.2%; n=459), data related to a higher prevalence of ASD in boys; 296 requests were for medications, totaling 100 distinct products, which demonstrates the diversification of requests within this specific scope; and There were 566 requests for medical assistance, of which 243 were for Multidisciplinary Treatment, which includes professionals from different fields of health, education, and developmental specialties, according to the patient’s individual needs. The study revealed that the analyzed processes follow a pattern quite different from the demands of adults, adding information to the current debate on the judicialization of health and justifying the strategic role of the Child and Youth Health Center 4.0, the most frequent causes of action and requests account for the majority of the processes, and, having identified this pattern, the research can support the formulation and implementation of public and judicial policies aimed at its prevention. It is noteworthy that the study relies on data from a single state and a specific time period. Future studies, especially longitudinal analyses or those involving other regions of the country, may broaden the understanding of the phenomenon and strengthen the conclusions.